Teachers and Technology in Rural Malaysian Classrooms: Insights from the T4 Teachers and Technology Global Survey - James, Cynthia; Hennessy, Sara (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Research Instruments Pack - Chachage, Kristeen; Hennessy, Sara; Koomar, Saalim; Swai, Calvin; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; Mrosso, Vicky; et al. (EdTech Hub, 2025)
This pack contains links to research instruments developed by EdTech Hub, the University of Dodoma, Aga Khan University, and Tanzania Institute of Education for the second phase of a study investigating the scale-up and local contextualisation of a national technology-supported teacher professional development programme known as MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, which translates as ‘teacher continuous professional development’ [TCPD] in English). The instruments draw on previously published research instruments used in Phase 1 of our research, plus examples from other sources that exemplify best practices in education research. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Usawa na maamuzi katika Mafunzo Endelevu ya Walimu Kazini yanayowezeshwa na Teknolojia nchini Tanzania: Zana za utafiti - Chachage, Kristeen; Swai, Calvin; Rwambali, Innocent; Hennessy, Sara; Koomar, Saalim; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; et al. (EdTech Hub, 2025)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Chuo Kikuu cha Dodoma, Chuo Kikuu cha Aga Khan, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza upanuzi na mabadiliko ya kuendana na mahitaji ya walimu na mazingira ya shule katika utekelezaji wa Mafunzo Endelevu ya Walimu Kazini (MEWAKA) unaojumuisha matumizi ya teknolojia. Katika kuandaa zana hizi, tumetumia zana zilizochapishwa katika awamu ya kwanza ya utafiti huu na mifano kutoka sehemu mbalimbali, kwa kuzingatia mifano mizuri ya utafiti kuhusu elimu. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Usawa na Maamuzi ya Walimu katika Mafunzo ya Walimu yanayosaidiwa na Teknolojia nchini Tanzania Muhtasari wa Mapendekezo ya Kisera ya Awamu ya Pili [Rasimu] - Chachage, Kristeen; Swai, Calvin; Hennessy, Sara; Adam, Taskeen; Koomar, Saalim; Paskali, J.H.; Mtenzi, Fredrick; Komba, Aneth; Jacob Mrope, Winifrida; Anthony, Gervace; Malibiche, Mustapha; Mrosso, Vicky; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Phase 2 Round 2 Recommendations - Chachage, Kristeen; Swai, Calvin; Hennessy, Sara; Adam, Taskeen; Koomar, Saalim; Hegwa Paskali, Jonathan; Massam, Winston; Mtenzi, Fredrick; Komba, Anneth; Jacob Mrpoe, Winfrida; Anthony, Gervace; Malibiche, Mustapha; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence